Outcome of Oligonodular Hepatocellular Carcinoma after Hepatectomy - Hossain, SM Shakhwat; Hasan, Md Mahboob; Rahman, Md Mahbubur (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Hepatocellular carcinoma (HCC) is a common cancer and is the third most common cause of cancer-related death worldwide. Frequent recurrence of HCC after resection is a major surgical limitation. Early recurrence is the most disappointing outcome after surgery for multinodular HCC. Several studies found good results after hepatectomy for oligonodular (2 or 3 nodules) HCC. Objectives: To observe the recurrence rate three months after hepatectomy for oligonodular HCC and study the possible risk factors. Materials and Methods: The study population consisted of 102 patients with oligonodular HCC and received hepatectomy in Combined Military Hospital (CMH) between July 2011 and July 2017 according to the following criteria: (1) numbers of tumour nodules determined by preoperative imaging (computed tomography or magnetic resonance imaging) and intraoperative exploration; (2) diagnosis of HCC confirmed by postoperative histopathology; (3) incision margins negative; (4) complete clinicopathologic data; (5) adjuvant chemotherapy advised one month after operation. Multicentric occurrence (MO) and intrahepatic metastasis (IM) were determined in each patient according to the histopathologic examination. Results: Among 102 patients, 43(42.2%) had small tumor stain three months after surgery, 22(21.6%) and 21(20.6%) were definded as single and multiple recurrence respectively. The recurrence rate of patients with microvascular involvement was higher (64.3%) than those without (33.8%), (p<0.05). IM or MO, complete tumor capsule or not, number of tumors (2 versus 3), liver condition (cirrhosis versus chronic hepatitis) showed no significant difference. Conclusion: There was a high rate of very early recurrence for patients with oligonodular HCC three months ater hepatectomy, and the hepatic resection seems no-account for these patients regardless of very early recurrence or not a curative resection. Microvascular involvement was a risk factor while IM or MO is not. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 55-57